Acute and Short-term Results of MitraClip XTR vs. PASCAL Transcatheter Valve Repair System for Edge-to-Edge Repair of Severe Tricuspid Regurgitation. Issue 5 (3rd September 2021) - Löw, Kornelia; Orban, Mathias; Stocker, Thomas; Mehr, Michael; Deseive, Simon; Gmeiner, Jonas; Hagl, Christian; Massberg, Steffen; Näbauer, Michael; Hausleiter, Jörg; Braun, Daniel
ABSTRACT: Background: Novel device developments enable the edge-to-edge treatment of inoperable patients with severe tricuspid regurgitation (TR) and large coaptation gaps. We compared the acute and short-term results of patients treated with the MitraClip XTR vs. PASCAL system. Methods: We retrospectively analyzed 120 patients (72 pts. MitraClip XTR, 48 pts. PASCAL) treated for isolated severe TR on a compassionate-use basis. Results: Mean patient age was 77 ± 8 years and the LaPar risk score was 6.7 ± 1.7%. Patients in the PASCAL group had a larger coaptation gap and a trend to more severe TR. Procedural success (TR ≤ 2) was achieved in 92% of patients in each group (XTR group: 66/72, PASCAL group: 44/48). Thirty-day follow-up was available in 94% of patients. Two patients in the PASCAL group and one patient in the MitraClip XTR group died within 30-days of the procedure. Device complications were observed in 15.3% of patients in the XTR group and in 10.4% of patients in the PASCAL group. There was a trend for a more pronounced reduction of vena contracta width in the PASCAL group compared to the XTR group. Tricuspid repair was associated with a comparable improvement in New York Heart Association (NYHA) functional class and 6-minute walking distance in both groups. Conclusion: The PASCAL and the MitraClip XTR system appeared to be highly efficacious in treating patients with severe TR with a comparable rate of device complications in both groups but a trend for a more pronounced reduction of vena contracta width in the PASCAL group. Abbreviations: CABG: Coronary artery bypass graft, EROA: Effective regurgitant orifice area; ICD: Implantable cardioverter-defibrillator, LVEF: Left ventricular ejection fraction. MACCE: Major adverse cardiac and cerebrovascular events; MLHFQ: Minnesota Living With Heart Failure Questionnaire; MR: Mitral regurgitation; NYHA: New York Heart Association; RV/RA gradient: Right ventricular/right atrial gradient. SLDA: Single leaflet device attachment; STVR: Surgical tricuspid valve repair; TR: Tricuspid regurgitation